2014
DOI: 10.1136/postgradmedj-2012-131428
|View full text |Cite
|
Sign up to set email alerts
|

Recreational drug use in men who have sex with men (MSM) attending UK sexual health services is significantly higher than in non-MSM

Abstract: Both lifetime and last month use of most recreational drugs was more common in MSM, when compared to non-MSM males. Sexual health clinics may provide an opportunistic encounter to identify patterns of recreational drug use, explore motivations for use, and implement strategies to reduce harms related to drug use. This will require a multidisciplinary approach to address the psychosocial aspects of drug taking behaviours, in combination with healthcare professionals experienced in the management of recreational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 24 publications
4
59
0
1
Order By: Relevance
“…Self-reported surveys of convenience samples have consistently found that use of recreational drugs in the LGBT population is significantly higher than among WSW or heterosexual adults (53,54), . This pattern is also replicated in MSM attending sexual health clinics (55). A systematic review of 23 studies found only use of methamphetamine and binge alcohol consumption to be significantly associated with increased sexual risk (56).…”
Section: Identification Of Problematic Recreational Drug and Alcohol Usementioning
confidence: 67%
“…Self-reported surveys of convenience samples have consistently found that use of recreational drugs in the LGBT population is significantly higher than among WSW or heterosexual adults (53,54), . This pattern is also replicated in MSM attending sexual health clinics (55). A systematic review of 23 studies found only use of methamphetamine and binge alcohol consumption to be significantly associated with increased sexual risk (56).…”
Section: Identification Of Problematic Recreational Drug and Alcohol Usementioning
confidence: 67%
“…[2] It is recognised that MSM are more likely to take drugs than the general population. [3] In the United States and Australia the practice is known as 'party and play' (PNP) and is more common in urban areas with a large gay population. [4,5] Whilst chemsex is not a new phenomenon, healthcare professionals are worried that increased availability and accessibility of drugs and sex through websites and mobile applications has increased the acceptability, fashionableness and incidence of chemsex.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns are echoed in a survey of attendees at genito-urinary clinics in July-September 2011 conducted in London which found higher rates of lifetime and last month use of both GHB and GBL by gay men than in heterosexual males. Lifetime use of GHB and GBL amongst gay men was 22.7% and 16.1% respectively; last month rates were 2.4% and 3.1% (Hunter et al, 2014). Lifetime use of GHB/GBL amongst gay males in the south London boroughs of Lambeth, Southwark and Lewisham between August 2013 and March 2014 was 30.6%, with 20.1% using in the previous year and 10.5% in the previous 4 weeks (Bourne et al, 2014).…”
Section: Recreational Use In the Ukmentioning
confidence: 99%